Interactions between fiscal multipliers and sovereign risk premium during fiscal consolidation: model based assessment for the euro area - Magdalena Lalik (European Central Bank (ECB), 2017)
The paper presents a model-based assessment of fiscal multipliers operating in the euro area during the period 2011-2014. The assessment is conditional on two distinct reactions of the sovereign risk premium (either responding endogenously to fiscal shocks or being an exogenous process) and two types of monetary policy (accommodative and non-accommodative). Applying those multipliers to the amount of austerity measures implemented in years 2011-14, the paper evaluates their possible fallouts and shows that the output effects of the recent fiscal consolidations were largely determined by two key factors: financial markets' sentiments and the composition of adopted measures. Finally, the paper also highlights the importance of modelling of government's interest payments for predicting the evolution of debt-to-GDP ratios.
Keywords: E42; E32; F42; F45; 330; debt dynamics; euro area; Fiscal multiplier; macroeconomic models; sovereign risk premium